Optimization of Sumatera Bentonite by Ammonium-impregnated as a Coagulant for Cassava Wastewater Treatment - Yusuf Mathiinul Hakim; Mokhamad Yusup Nur Khakim; Amatullah Hanifah; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
The original Sumatera Bentonite (SB), which has been impregnated to be ammonium bentonite (NH-B), was applied as a cassava wastewater coagulant. The modification was conducted using multi-step impregnation initiated by bentonite activation (sodium cation exchange), followed by ammonium impregnation. The optimization parameter focused on the coagulant dose that was used. The result of cassava wastewater coagulation by the ammonium-impregnated bentonite (with dose: 0.4 g/100 mL) shows high-efficiency reduction for turbidity up to 73.97% (from 1099 to 186 NTU), Total Suspended Solid up to 86.56% (from 588 to 79 mg/L), and Chemical Oxygen Demand up to 88.6% (from 559.7 to 63.3 mg/L). The existence of ammonium impregnated is characterized by X-Ray Diffraction analysis based on 2theta shifting at 10° and Fourier Transform Infra-Red analysis at 464, 521, and 1429 cm−1 as ammonium binding.